Disparties in fruit and vegetable intake by Socio-demographic characteristics in peri-urban Nepalese adults: findings from the Heart-health Associated Research and Dissemination in the Community (HARDIC) Study, Bhaktapur, Nepal - Vaidya, A; Oli, N; Aryal, UR; Karki, DB; Krettek, A (Journal of Kathmandu Medical College, 2014)
Background: Inadequate fruit and vegetable intake and other adverse dietary habits – along with tobacco and alcoholabuse and sub-optimal physical activity - make up the four most important behavioural risk factors of non-communicablediseases. Low fruit and vegetable intake is particularly associated with burden of high cardiovascular disease. It hasreceived more attention in the last decade, with studies that explore disparities and determinants in their intake, as wellas interventions that attempt to improve the intake. Objectives: Our study aimed to determine fruit and vegetable consumption in a peri-urban community of Nepal and tocompare this intake in relation to various socio-demographic variables. Methods: This cross-sectional study was conducted as a part of the HARDIC (Heart-Health Associated Research andDissemination in the Community) study in the Jhaukhel-Duwakot Health Demographic Surveillance Site in the Bhaktapurdistrict of Nepal during September-December 2011. Adults from six randomly selected clusters were interviewed by 12trained interviewers after taking informed consent. WHO-STEPS questions were used to elicit information on fruit andvegetable intake. Results: Fruit and vegetable intake in the community was low with 2.1 percent of the study population consumingthe WHO-recommended fi ve servings per day. There were differences in the intake according to the various sociodemographicfactors. Conclusions: Our study reaffi rms low fruit and vegetable intake as a public health problem in the Nepalese context.Health-promotional activities aimed at specifi c target groups are essential. Multi-sectoral coordination of health andother health-related sectors is therefore vital in addressing the issue. DOI: http://dx.doi.org/10.3126/jkmc.v2i1.10512 Journal of Kathmandu Medical College, Vol. 2, No. 1, Issue 3, Jan.-Mar., 2013, Page: 3-11